Handheld Weights as an Effective and Comfortable Way To Increase Exercise Intensity of Physical Activity in Virtual Reality: Empirical Study - Jacek Polechoński; Anna Zwierzchowska; Łukasz Makioła; Dorota Groffik; Karolina Kostorz (JMIR Publications, 2022)
BackgroundIn recent years, there has been a growing interest in active virtual reality games (AVRGs) that provide entertainment and encourage more physical activity (PA). Since playing AVRGs involves primarily arm movements, the intensity of this form of PA may not be sufficient for health benefits. Therefore, it is worth looking for virtual entertainment solutions that are comfortable for users and at the same time increase physical exercise. ObjectiveThe main objective of this study was to evaluate the effect of external loading of the arms in the form of handheld weights (HHWs) on exercise intensity in users playing a popular AVRG. The results obtained in the study were compared with the PA recommendations for health. The study also assessed the perceptions of the users about the attractiveness and usefulness of this type of exercise and discomfort caused by additional load on the arms. MethodsThe study covered 17 young adults aged 18 to 25 years playing an AVRG (Beat Saber) with no arm load and with HHWs (0.5 kg). A PlayStation 4 PRO console (Sony) with accessories including a head-mounted display and controllers was used in the study. PA intensity was evaluated using a heart rate monitor based on the percentage of maximal heart rate (% HRmax). The usability, attractiveness, and comfort perceived during exercise by users were evaluated using a survey questionnaire. ResultsThe measurements showed that the mean % HRmax in participants playing Beat Saber without HHWs was significantly lower (P<.001; Cohen d=1.07) than that observed when playing with HHWs. It should be emphasized that with no additional load, the intensity of PA was low (mean 63.7% HRmax, SD 9.3% HRmax), while with the upper limb load, it increased to a moderate level (mean 67.1% HRmax, SD 10.3% HRmax), which is recommended for health benefits. The survey conducted in the study showed that HHWs (0.5 kg) attached to the wrists did not disturb Beat Saber players. ConclusionsSince PA in most of the modern AVRGs primarily involves upper limb movements, the use of HHW seems to be a simple and effective way to increase exercise intensity, especially because, as reported by the study participants, such a procedure does not cause discomfort while using the application.